2015
DOI: 10.1039/c5tb00621j
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of osteogenesis and angiogenesis of icariin loaded on micro/nano hybrid structured hydroxyapatite granules as a local drug delivery system for femoral defect repair

Abstract: Icariin has been identified to promote osteogenic differentiation of bone mesenchymal stem cells (BMSCs). However, whether icariin could enhance angiogenic factor expression of BMSCs, which may be vital for bone repair, needs to be explored. Moreover, how to construct a delivery system of icariin and its repair capability in bone defects are still unknown. In the present study, the effects of icariin on the osteogenic differentiation and angiogenic factor expression of BMSCs were firstly evaluated.Moreover, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…These results validated earlier studies that reported that BCP is the ideal choice of scaffolds for tissue-engineered bone (12,13,15). HA, with a calcium to phosphorus ratio (Ca/P) of 1.67, is considered to be the stable phase and is hardly absorbed, which may be an obstacle for its use in bone regeneration (42,43). By contrast, β-TCP, with a Ca/P ratio of 1.5, was easily absorbed (43).…”
Section: Discussionmentioning
confidence: 99%
“…These results validated earlier studies that reported that BCP is the ideal choice of scaffolds for tissue-engineered bone (12,13,15). HA, with a calcium to phosphorus ratio (Ca/P) of 1.67, is considered to be the stable phase and is hardly absorbed, which may be an obstacle for its use in bone regeneration (42,43). By contrast, β-TCP, with a Ca/P ratio of 1.5, was easily absorbed (43).…”
Section: Discussionmentioning
confidence: 99%
“…Different researchers have used various biogenic resources for the extraction of HAp. Barakat et al [18] and Sofronia et al [19] used bovine bones, Lu et al [20] used pig bone and teeth, and Abdulrahman et al [21], Wu et al [5], and Khandelwal and Prakash [1] used wastes from eggshells. Similarly, Ferreira et al [22] extracted from ostrich eggshells.…”
Section: Introductionmentioning
confidence: 99%
“…It is a calcium/phosphate-based bioceramic which is chemically like the inorganic constituent of the bone matrix (a very complex bone tissue) with the general formula Ca 10 (PO 4 ) 6 (OH) 2 [ 4 ]. This ceramic is not only biocompatible, osteoconductive, noninflammatory, and nonimmunogenic but also bioactive; i.e., it has an ability to form a direct bond with living tissues and promote tissue growth [ 5 ]. Owing to these properties and chemical likeness to the mineral constituent of the bone matrix, it is a prime filler material to replace damaged bone or is a coating on implants to promote bone ingrowths into prosthetic implants and many more non-load bearing applications [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more attention has been focused on the HAp with nanostructures surfaces because it can increase specific surface area and surface energy of the material and the structure of pore space itself can promote cell viability, migration and differentiation [17]. In addition to above advantage, nano-HAp particulates also showed the function of adsorbing and releasing drugs along with osteogenic and angiogenic effects through loaded icariin [18] and quercetin [19], etc. However, the local application of SrR in animal models of osteoporosis and new nano-HAp particulates loaded SrR has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%